An examination and proposed definitions of family members' grief prior to the death of individuals with a life-limiting illness: A systematic review. (April 2022) - Singer, Jonathan; Roberts, Kailey E; McLean, Elisabeth; Fadalla, Carol; Coats, Taylor; Rogers, Madeline; Wilson, Madeline K; Godwin, Kendra; Lichtenthal, Wendy G
Background: Research has extensively examined family members' grief prior to the death of an individual with a life-limiting illness but several inconsistencies in its conceptualization of related constructs, yet significant conceptualization issues exist. Aim: This study aimed to identify and characterize studies published on family members grief before the death of an individual with a life-limiting illness, and propose definitions based on past studies in order to initiate conceptual clarity. Design: A mixed-method systematic review utilized six databases and was last conducted July 10, 2021. The search strategy was developed using Medical Subject Headings. This study was prospectively registered on PROSPERO (CRD42020166254). Results: One hundred thirty-four full-text articles met inclusion criteria. This review revealed across studies a wide variation in terminology, conceptualization, and characterization of grief before the death. More than 18 terms and 30 definitions have been used. In many cases, the same term (e.g. anticipatory grief) was defined differently across studies. Conclusions: We found grief occurring before the death of a person with a life-limiting illness, which we termed pre-death grief, is comprised of two distinct constructs: anticipatory grief and illness-related grief. Anticipatory grief is future-oriented and is characterized by separation distress and worry about a future without the person with the life-limiting illness being physically present. Illness-related grief is present-oriented and is characterized by grief over current and ongoing losses experienced during the illness trajectory. These definitions provide the field with uniform constructs to advance the study of grief before the death of an individual with a life-limiting illness.